Correlation of cytomorphology with flowcytometric immunophenotyping in patients of acute leukemia in tertiary care hospital (Journal of Pathology of Nepal, 2022)
Background: Morphological diagnosis of leukemias may sometimes not correlate with flow cytometry diagnosis. Classification of hematological neoplasm by the World Health Organization gives priority to cytogenetic, molecular biology, and even patient history, in an attempt to classify patients primarily regarding prognosis. Cytomorphology and immunophenotyping complement each other. Morphology is burdened by a high degree of subjectivity. That is why correlation of information provided by the two techniques is still absolutely necessary. The aim of our study was to correlate between cytomorphological findings and immunophenotyping results on a group of patients investigated for acute leukemia.Materials and Methods: Study was conducted in department of pathology in Chirayu Medical College and Hospital, Bhopal from December 2018 to September 2019. Cases were diagnosed as acute leukemia based on complete blood count and bone marrow aspirate/peripheral smear.These cases were sent to flowcytometry for immunophenotyping for further confirmation.Results: Total 74 cases of acute leukemias were diagnosed, out of which 30 were Acute myeloid leukemia and 44 were Acute lymphoblastic leukemia. There was 95.95% correlation between diagnosis on cytomorphology and flowcytometry. Two cases remain unclassified on cytomorphology which turn out to be Acute myeloid leukemia on flowcytometry. One case of Acute myeloid leukemia on cytomorphology was diagnosed as Acute lymphoblastic leukemia on flowcytometry.Conclusions: Inclusion of flowcytometry in routine diagnostic workup of acute leukemia ensures proper characterization as well as management. Major challenges for the near future are the standardization of technical procedures, data interpretation, and reporting.